1986
DOI: 10.1017/s0003356100002671
|View full text |Cite
|
Sign up to set email alerts
|

A study of sexual development in ram lambs

Abstract: Two experiments were designed to study the effect of rearing method, female company, and repeated libido and semen tests on the pattern of sexual development of ram lambs. Four artificial rearing treatments (AR) were compared with natural rearing (NR) in one experiment and four artificial compared with three natural rearing treatments in a second experiment. Lambs on AR treatments in both experiments, as well as naturally reared lambs in the second experiment, were reared with or without females either before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Al-Nakib et al [30] observed that lambs reared with their mother presented an earlier sexual development and a delayed sexual interest in oestrus ewes compared to artificially reared lambs. However, it is important to highlight that in the study of Al-Nakib et al [30] the amount of food that was offered to lambs artificially reared was not adjusted in relation to that received by lambs reared with their mothers, and thus, lambs reared with their mothers had greater body weight than those reared artificially. Although there were differences between both groups of lambs, in male lambs, prepuberal reproductive development is strongly influenced by body weight [31,32], confounding both effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Al-Nakib et al [30] observed that lambs reared with their mother presented an earlier sexual development and a delayed sexual interest in oestrus ewes compared to artificially reared lambs. However, it is important to highlight that in the study of Al-Nakib et al [30] the amount of food that was offered to lambs artificially reared was not adjusted in relation to that received by lambs reared with their mothers, and thus, lambs reared with their mothers had greater body weight than those reared artificially. Although there were differences between both groups of lambs, in male lambs, prepuberal reproductive development is strongly influenced by body weight [31,32], confounding both effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Young bucks showed some inferiority in their fertilizing ability compared to the experienced mature adults, and the gap was even wider between rams and young ram lambs, making the use of ram lambs for breeding purposes inadvisable. This problem in young ram lambs has been identified by many breeders and research workers (Dyrmundsson & Lees 1972;Zenchak & Anderson 1980;Al-Nakib et al 1986). The latter authors attributed this problem to the social environment under which these animals were reared, which adversely affected body growth and hence other correlated traits directly involved in sexual development.…”
Section: Discussionmentioning
confidence: 99%
“…Puberty can be defined as the time period when fertile spermatozoa are present intheejaculate (Beardenand&Fuquay 1997). Many sheep producers tend to use a relatively high percentage of ram lambs in their breeding program by 7 months of age (Al-Nakib et al 1986). Thus, they benefit from accelerating genetic improvement by using young rams for breeding (Price et al 1991).…”
Section: Introductionmentioning
confidence: 99%